Note from the editor: The Brave New World of Big Data - Ákos Róna-Tas (economic sociology_the european electronic newsletter, 2019)
This issue is organized around the theme of Big Data as our new social world, one that has been taking shape thanks to three important recent advances in information technology, all accelerated in the last few years.
Keywords: 300